Ultimate gig : flexibility, freedom, rewards - Fleming, John T.; Head, Lauren Lawley (Emerald Publishing Limited, 2021)
The gig economy can be viewed as the fuel that lit the fire of change in economies throughout the world. Flexible work grew out of a cultural shift in how we defined how we wished to work. The gig economy also grew out of a need, a need to earn more to keep pace with the inflation that nullified expected gains in purchasing power as wages increased. We no longer define work as related to the brick and mortar buildings that housed the traditional 9 to 5 job. Perhaps, the office-centric era is over as many companies have now made decisions relative to how and when their employees can work. Work from home is no longer a wish; it is a reality, and the gig economy has been the fuel that has helped companies realize new and better ways to engage labor and serve consumers. The future has arrived! The marketplace is favorable to new ways to purchase products and services. Gig opportunities will continue to grow as a meaningful way to earn income. The ultimate gig is ultimately the one that best matches the gig seeker's definition of what matters most. Our ultimate motivation for taking on the work of this book, this research project, is rooted in a belief that the gig economy is helping to define a new reality; flexibility and freedom in how work is done can be achieved. We believe in the free enterprise system. When we focus on contribution, we best explore the possibilities that improve the quality of any product or service and the quality of all the lives we touch.
Includes index.
Keywords: Work.; Precarious employment.; Temporary employment.; Independent contractors.; Business & Economics -- Marketing / Multilevel.; Business strategy.; elektronické knihy; electronic books